1999
DOI: 10.1046/j.1442-2050.1999.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Mallory–Weiss syndrome in children

Abstract: The aim of the study was to evaluate the incidence and the etiology of Mallory-Weiss syndrome in children. The study population comprised 2720 children aged 5 months to 18 years who had undergone upper gastrointestinal endoscopy. Mallory-Weiss syndrome was diagnosed in eight (0.3%) of the examined children. Endoscopic examination in five of them revealed linear mucosal tears, mostly above and in one case also below the gastroesophageal junction. In three children a linear scar in the lower portion of the esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…The results of studies have shown that the most common cause of upper GI bleeding in newborn infants and children younger than 2 years are maternal blood ingestion, and gastritis or stress ulcers, respectively ( 10 , 18 , 19 ). Mallory-Weiss tear was also more prevalent in older children ( 20 , 21 ). But, our findings showed that the most common causes of bleeding in upper GI system are coagulopathy and maternal blood ingestion in newborns, while esophagitis and prolapse gastropathy are the most important etiology of GI bleeding in children younger than 5 years old.…”
Section: Discussionmentioning
confidence: 95%
“…The results of studies have shown that the most common cause of upper GI bleeding in newborn infants and children younger than 2 years are maternal blood ingestion, and gastritis or stress ulcers, respectively ( 10 , 18 , 19 ). Mallory-Weiss tear was also more prevalent in older children ( 20 , 21 ). But, our findings showed that the most common causes of bleeding in upper GI system are coagulopathy and maternal blood ingestion in newborns, while esophagitis and prolapse gastropathy are the most important etiology of GI bleeding in children younger than 5 years old.…”
Section: Discussionmentioning
confidence: 95%
“…Back-Lomaniszyn et al. reported that MWS accounts for 12.8% of pediatric patients with upper gastrointestinal bleeding [ 1 ]. One reason for the rarity of this condition is that children rarely consume alcohol, which is known to trigger MWS [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mallory–Weiss syndrome (MWS) is a condition, in which a sudden increase in intragastric pressure causes laceration of the mucosa near the esophagogastric junction. It is a rare cause of hematemesis in infancy [ 1 ]. Although it can sometimes cause anemia or even shock because of severe bleeding, no case of infant with MWS complicated with severe aspiration pneumonitis has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…sont observés chez l'enfant [20,21]. Le syndrome de Mallory-Weiss est la cause de 5 à 15 % des hémorragies digestives hautes [13,14,20,[22][23][24][25][26][27] ; les chiffres des plus grandes séries tournant autour de 6-8 %.…”
Section: Le Syndrome De Mallory-weiss Prédomine Chez Les Hommes Et Leunclassified